Integração da análise SWOT com o método ELECTRE TRI na avaliação do desempenho de programas de pós-graduação - Neves, Roberta Braga (2006)
This work investigates the integration of Analysis SWOT, a tool of Strategical Planning, to a method of Aid Multicriteria to the Decision, ELECTRE TRI. The basis of the study was a bibliographic research used in two axles related to the objective of the main topic:strategical planning and aid multicriteria to the decision. In this way, it was arrived a satisfactory modeling for the problem. The present research also analyses the application of this integration in a specific case of evaluation and classification of performance and strategical positioning of the Program of Undergraduation in Engineering of Production of the University Federal Fluminense. This application was effected at four moments. First the bibliographical survey was made. Later, data were collected through a questionnaire considered and sent for e-mail or applied personally to the coordinators, professors, students and postgraduates of the Program. At a third moment the classification of the Program in classrooms was effected. Finally, conclusions are presented, detaching the difficulties and the positive points of this boarding. It is worth to stand out that the gotten results indicate the viability of the proposal presented in the research.